STYLISTIC APPROACH TO TEACHING POETRY IN ESL CLASSROOMS - Tahmasebi, Leila (Journal of process management and new technologies, 2019)
In this study it has been tried to illustrate the importance of stylistic approach in teaching literature in general and poetry in particular. The context of the study is classrooms of non- English universities. The objective is inducing critical thinking and purposeful essay writing based on linguistic features of texts. Initially by having a glimpse at the style and stylistics, we try to have an overall understanding of stylistics. Deviation and foregrounding the important elements of stylistics are discussed next. Following the introductory section, the main question and the thesis of the paper, the importance of application of stylistics approach in teaching literature in ESL classes, is discussed. The pace of the paper is towards a practical exploration of the topic, hence, ESL classroom analysis procedure and levels of the procedure are manifested. The closing section of the paper is a short analysis of a poem by E. E. Cummings based on stylistic approach and its two basic aspects, deviation and foregrounding. In this section the aim is coming to a comprehensive and practical conclusion about stylistic approach in teaching poetry.